Net community production at Ocean Station Papa observed with nitrate and oxygen sensors on profiling floats. Issue 6 (22nd June 2016) - Plant, Joshua N.; Johnson, Kenneth S.; Sakamoto, Carole M.; Jannasch, Hans W.; Coletti, Luke J.; Riser, Stephen C.; Swift, Dana D.
Abstract: Six profiling floats equipped with nitrate and oxygen sensors were deployed at Ocean Station P in the Gulf of Alaska. The resulting six calendar years and 10 float years of nitrate and oxygen data were used to determine an average annual cycle for net community production (NCP) in the top 35 m of the water column. NCP became positive in February as soon as the mixing activity in the surface layer began to weaken, but nearly 3 months before the traditionally defined mixed layer began to shoal from its winter time maximum. NCP displayed two maxima, one toward the end of May and another in August with a summertime minimum in June corresponding to the historical peak in mesozooplankton biomass. The average annual NCP was determined to be 1.5 ± 0.6 mol C m −2 yr −1 using nitrate and 1.5 ± 0.7 mol C m −2 yr −1 using oxygen. The results from oxygen data proved to be quite sensitive to the gas exchange model used as well as the accuracy of the oxygen measurement. Gas exchange models optimized for carbon dioxide flux generally ignore transport due to gas exchange through the injection of bubbles, and these models yield NCP values that are two to three time higher than the nitrate‐based estimates. If nitrate and oxygen NCP rates are assumed to be related by the Redfield model, we show that the oxygen gas exchange model can be optimized by tuning the exchange terms to reproduce the nitrate NCP annual cycle. Key Points: Net community production (NCP) was measured over 6 years with chemical sensors on six profiling floats NCP rates remained positive from middle winter to autumn Linking nitrate‐ and oxygen‐based NCP rates allow gas exchange parameterizations to be optimized